2019
DOI: 10.1101/735050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the mycobiome of the seagrass,Zostera marina, reveals putative associations with marine chytrids

Abstract: 42Seagrasses are globally distributed marine flowering plants that are foundation species in coastal 43 ecosystems. Seagrass beds play essential roles as habitats and hatcheries, in nutrient cycling and 44 in protecting the coastline from erosion. Although many studies have focused on seagrass 45 ecology, only a limited number have investigated their associated fungi. In terrestrial systems, 46 fungi can have beneficial and detrimental effects on plant fitness. However, not much is known 47 about marine fungi … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 103 publications
8
44
1
Order By: Relevance
“…Chytridiomycota were found to be prevalent members of the Z. marina leaf microbiome in Ettinger & Eisen (2019), however, no chytrids were cultured in this study. This is likely because the isolation methods used here favor cultivation of Dikarya.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Chytridiomycota were found to be prevalent members of the Z. marina leaf microbiome in Ettinger & Eisen (2019), however, no chytrids were cultured in this study. This is likely because the isolation methods used here favor cultivation of Dikarya.…”
Section: Discussioncontrasting
confidence: 54%
“…are drivers of the positive relationship observed previously between the number of tissue types and number of media types a fungal genus was isolated from ( Figure S2). Ettinger & Eisen (2019) We compared the diversity of the fungi isolated here to high throughput sequencing data associated with Z. marina from the same location (as previously analysed in Ettinger & Eisen (2019). We found that the fungal genera isolated in this study were generally also detected in the sequencing data (Table 1).…”
Section: Phylogenetic Comparison Of Fungal Isolates Across Seagrass Smentioning
confidence: 58%
See 3 more Smart Citations